Factors Influencing Parents’ Decisions on Choosing an Islamic Primary School in Bandung Indonesia - Dian Hidayati; Andi Arif Rifa’i (RIRAI Publisher, 2020)
The era of disruption has brought about the impact of fundamental changes in the digital-based information presentation globally. Easy access to information and communication through social networks makes children no longer care about the surrounding environment and tends to be